Solubility Modelling pf Butterfly Wing Leaves (Christia Vespertilionis) in Supercritical Carbon Dioxide - A. A. Hamid, Izni; Ismail, Norhuda; N. Mustapa, Ana; A. Rahman, Norazah (International Journal of Engineering and Technology, 2018)
Medicinal herb Christia vespertilionis oil has been claimed to possess anti-cancer and anti-plasmodial properties and show interest in food and pharmaceutical industries. Being an important alternative medicine plant, solubility data of Christia vespertilionis oil is demanded in order to understand the separation process and is crucial for designing purposes. In this work, extraction and determination of the oilâ€™s solubility were carried out using a green technique of supercritical carbon dioxide at a temperature range of 40 to 60â„ƒ and 276 to 414 bar of pressure. The results demonstrated that the highest solubility was obtained at the highest temperature and pressure of 60â„ƒ and 414 bar, respectively. For solubility prediction, experimental data were modelled using four empirical density-based models: Chrastil, del Valle and Aguilera, Adachi and Lu, and Sparks et al. models. In general, all the models were able to predict the solubility of Christia vespertilionis oil in supercritical carbon dioxide. The best fitting showed that Adachi and Lu model gave the best correlation with the lowest %AARD value of 1.61%.Â Â